AGBIOTECH - NEWS AND INFORMATION - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
CAB International publishes this new bulletin of biotechnology abstracts bi-monthly. There is a selection of the most recent scientific articles on application, methods, and research in biotechnology. CAB Intemational - Wallingford Oxon OX10 8DE- UK